STRUKTUR DAN DISTRIBUSI PENDAPATAN PETANI KELAPA SAWIT POLA PIR DI DESA MEKAR JAYA KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Sijabat, Afriani; Edwina, Susy; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Scheme smallholder is one of development pattern smallholders transmigration is the first development pattern smallholders which developed. This research aims to analyze palm oil plantation income, to analyze palm oil household income structure, and to analyze palm oil household income distribution. This reseacrh was implemented at Mekar Jaya Village. Kampar Kiri Tengah subdistrict by using survey method. The population of the farmer group is 405 people and 40 people from the palm oil groub was taken as samples by using slovin formula. The research result obtained that the average household income from pal oil plantation per month per hectare is Rp. 2.906.235 while per year is Rp. 34.874.825. income structure from oil palm plantation is 45,60 %, from non-agricultural such as trade is 26,68 %, also Index Gini Ratio is 0,164 which showed low inequality. The low inequality of palm oil household income at Mekar Jaya Village was caused by the existance of additional income so the household income of palm oil farmer is relatively better. Keyword : Income Structure, Distribution, Index Gini Ratio